A rare case of Bellini duct carcinoma - Genov, P.P. (Urol Case Rep, 2019)
We present a rare clinical case of renal cell carcinoma from the collection tubules-carcinoma of Bellini. A 69 years old patient, enters in our department with symptoms of massive hematuria. From the studies carried out-blood tests, CT and cystoscopy there are no data of neo process of lower urinary tract, but shows horseshoe-shaped kidney, cystic deformation of the left kidney and aortic dissection. A left radical nephroureterectomy was performed, with preoperative diagnosis of renal tumor at stage T3. The histopathological diagnosis was Bellini duct carcinoma of papillary tubular type. The patient currently remains disease –free.